1996
DOI: 10.1007/bf00185883
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bacterial communities from activated sludge: Culture-dependent numerical identification versus in situ identification using group- and genus-specific rRNA-targeted oligonucleotide probes

Abstract: The structures of bacterial communities were studied in activated sludge samples obtained from the aerobic and anaerobic zones of a wastewater treatment plant showing enhanced phosphorous removal. Samples were analyzed by in situ hybridization with oligonucleotide probes complementary to selected regions of the 16S and 23S ribosomal RNA (rRNA) characteristic for defined phylogenetic entities (genera and larger groups). The microbial community structures revealed by molecular techniques were compared with the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
87
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(99 citation statements)
references
References 59 publications
(61 reference statements)
8
87
1
1
Order By: Relevance
“…The Proteobacteria were the predominant group in our investigation, accounting for 45 (50%) of 90 sequences, consistent with other investigations reporting high prevalence (20-50%) of Proteobacteria in bacterial communities in aquatic habitats [2,3,18] such as seawater [15,33], decaying salt marsh grass [7], and wastewater [7]. In potable water distribution systems, many bacterial species, including members of the Proteobacteria, Actinobacteria, low-G+C-content gram-positive bacteria, and Cytophaga-Flavobacterium-Bacterioides group, readily adhere to surfaces to form multispecies biofilms [39].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The Proteobacteria were the predominant group in our investigation, accounting for 45 (50%) of 90 sequences, consistent with other investigations reporting high prevalence (20-50%) of Proteobacteria in bacterial communities in aquatic habitats [2,3,18] such as seawater [15,33], decaying salt marsh grass [7], and wastewater [7]. In potable water distribution systems, many bacterial species, including members of the Proteobacteria, Actinobacteria, low-G+C-content gram-positive bacteria, and Cytophaga-Flavobacterium-Bacterioides group, readily adhere to surfaces to form multispecies biofilms [39].…”
Section: Discussionsupporting
confidence: 92%
“…Our survey of field diversity of bacterial communities in human-made containers (n=52) and natural tree holes (n= 2) was conducted over a 3-day period from September [16][17][18]2003. Container-inhabiting Aedes mosquitoes are most abundant from July to October.…”
Section: Collection and Processing Of Samplesmentioning
confidence: 99%
“…This indicated that the majority of microbial community of the domestic process was accounted for by the group-specific probes, whereas 11% of the bacterial biomass of the industrial process was not accounted for. These populations could belong to other divisions such as the CFB phylum (Kämpfer et al 1996) and low G + C Gram-positive bacteria (Snaidir et al 1997) or even possibly hitherto undiscovered taxonomic ranks. It is also possible that upon acclimation, the industrial process could have selected for a highly specialized population that could not be detected by the group-specific probes used.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, culture dependant techniques such as most probable number (MPN) method and heterotrophic plate counts on enrichment media, have been used to characterize and enumerate these communities in activated sludge. However, only 15% of the indigenous bacteria in activated sludge could be cultivated (Wagner et al 1993;Kämpfer et al 1996). These limitations have lead to techniques using the 16S rRNA approach.…”
Section: Introductionmentioning
confidence: 99%
“…Often, these shifts result from population changes within the complex microbial community (Kampfer et al, 1996). However, it is possible that certain key bacteria also undergo natural genetic alterations.…”
Section: Introductionmentioning
confidence: 99%